2015
DOI: 10.1186/s13000-015-0428-4
|View full text |Cite
|
Sign up to set email alerts
|

Defining the value of CD56, CK19, Galectin 3 and HBME-1 in diagnosis of follicular cell derived lesions of thyroid with systematic review of literature

Abstract: BackgroundNodular follicular lesions of thyroid gland comprise benign and malignant neoplasms, as well as some forms of hyperplasia. “Follicular” refers to origin of cells and in the same time to growth pattern - building follicles. Nodular follicular thyroid lesions have in common many morphological features, therefore attempts were made to define additional criteria for distinction between follicular adenoma, follicular carcinoma and follicular variant of papillary carcinoma. Increasing number of immunohisto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
55
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 62 publications
8
55
1
1
Order By: Relevance
“…In the study by de Matos et al, as in our study, no staining was found in normal thyroid tissue [9]. Various studies demonstrated that Gal-3, in comparison to HBME-1 and CK19, has a higher sensitivity in distinguishing between benign and malignant lesions [7,12]. In our study, the sensitivity value of Gal-3 was lower than those of HBME-1 and CK19.…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…In the study by de Matos et al, as in our study, no staining was found in normal thyroid tissue [9]. Various studies demonstrated that Gal-3, in comparison to HBME-1 and CK19, has a higher sensitivity in distinguishing between benign and malignant lesions [7,12]. In our study, the sensitivity value of Gal-3 was lower than those of HBME-1 and CK19.…”
Section: Discussioncontrasting
confidence: 53%
“…There are many studies demonstrating the positivity of Gal-3 in malignant lesions of thyroid, especially CVPTC [7,8,9,10,22]. Furthermore, positivity with varying frequencies was reported in different studies in benign thyroid nodules and lesions, follicular adenoma and FVPTC [7,8,9,10,12,22]. In our study, we did not observe staining with Gal-3 in NT tissue, and in FND and FA.…”
Section: Discussionmentioning
confidence: 36%
See 2 more Smart Citations
“…[5] Upregulation of CK19 is connected with neoplastic transformation. [6] CD56 is a neural cell adhesion molecule (NCAM). [4] CD56 expression is markedly reduced by malignant transformation as previously reported in cases of FC, Anaplastic Carcinoma, and PC.…”
Section: Introductionmentioning
confidence: 99%